1997
DOI: 10.3406/ecmed.1997.1838
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la variété et du type de piège sur la courbe des vols de la mouche de l’olive Bactrocera oleae Gmel. dans la région de Ain Taoudjate au Maroc

Abstract: Ce travail a été réalisé dans le but de contribuer à la connaissance de l’influence de diverses variétés de l’olivier et du type de piège sur l’activité imaginale de Bactrocera oleae à Ain Taoujdate. Dans cette région, l’activité des adultes est concentrée pendant une période qui s’étend de l’automne au début du printemps. La variété ne semble pas avoir un effet sur l’allure de la courbe des vols de B. oleae. Les populations de l’insecte suivent des phases de vol conditionnées par les facteurs climatiques et p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several previous studies of the olive tree in various ranges worldwide, showed a relatively large infestation of olives by the larvae of B. oleaea in wetter areas, i.e., areas of high altitudes, irrigated orchards and coastal areas [13] [27] [28] In coastal areas, it is shown that the adults are active throughout the year, such as eggs and larvae can be detected in fruits left on the ground or which have fallen and left on the trees [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies of the olive tree in various ranges worldwide, showed a relatively large infestation of olives by the larvae of B. oleaea in wetter areas, i.e., areas of high altitudes, irrigated orchards and coastal areas [13] [27] [28] In coastal areas, it is shown that the adults are active throughout the year, such as eggs and larvae can be detected in fruits left on the ground or which have fallen and left on the trees [29].…”
Section: Discussionmentioning
confidence: 99%